Intelligence territoriale, acteurs et transformation - Bozzano, Horacio (2011)
At all levels, micro, meso and macro, the territories, through their evolution, are the scene of multiple interactions between institutional, social, economic and scientific actors. These interactions can be analyzed in three ways: a) the deployment of "axiological vectors" bearing on the territory itself, b) four capabilities: control adaptation, transformation and logusglobalisation and c) simultaneous modes of intervention: bottom-up and top-down. Case studies in Latin America, Europe and South America indicate variations in the matrix of actors and three axes of analysis aforementioned.